2021
DOI: 10.26434/chemrxiv.13615385.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Amyloid like Aggregates Formed by the Self-Assembly of Proline and Hydroxyproline

Abstract: <p>Single amino acid based self-assembled structures have gained a lot of interest recently owing to their pathological significance in metabolite disorders. There is plethora of significant research work which illustrate amyloid like characteristics of assemblies formed by aggregation of single amino acids like Phenylalanine, Tyrosine, Tryptophan, Cysteine and Methionine and its implications in pathophysiology of single amino acid metabolic disorders like phenylketonuria, tyrosinemia, hypertryptophanemi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…However, very recently, some nonaromatic amino acids have been reported to form similar fibrillar aggregates to that of aromatic amino acids. 9,16 For example, the nonaromatic amino acids, like methionine (Met), cysteine (Cys), proline (Pro), hydroxyproline (Hyp), etc. also form amyloid-like fibrillar deposition which is cytotoxic to cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, very recently, some nonaromatic amino acids have been reported to form similar fibrillar aggregates to that of aromatic amino acids. 9,16 For example, the nonaromatic amino acids, like methionine (Met), cysteine (Cys), proline (Pro), hydroxyproline (Hyp), etc. also form amyloid-like fibrillar deposition which is cytotoxic to cells.…”
Section: Introductionmentioning
confidence: 99%
“…Recently we also reported unusual aggregates formed by proline, hydroxyproline, and lysine which also revealed cytotoxicity to ShS5Y neural cell lines as confirmed by MTT assays. 11 Hence, motivated by the previous research studies and our own investigation on single amino acid self-assembly and its implications in diseases, we were motivated to study the aggregation properties of other non-aromatic amino acids (Gln, Ser, Thr, Ala, Asn, Arg, Asp, Glu) and one aromatic acid (His) extensively under varying concentration and ageing time. The excess of these amino acids in body causes disease conditions like hyperserinemia, 12 histidinemia 13 and threoninemia.…”
Section: Introductionmentioning
confidence: 99%
“…4 In the past few decades, there has been a considerable amount of research which is pursued in single amino acids and modified single amino acids. [5][6][7][8][9][10][11][12] In this context, Gazit et al reported amyloid-like structure formed by phenylalanine, 5 tyrosine 6 , and tryptophan. 7 Sarkar et al reported the fibrillar structure of glycine.…”
Section: Introductionmentioning
confidence: 99%
“…13 Wangoo and co-workers demonstrated the self-assembly of aromatic single amino acids, [14][15][16] and studied them extensively via various biophysical assays such as FTIR, NMR, TGA, and XRD. 8,9,13,14 Scheme 1: Chemical structure of Z-Phe-OH, Z-Trp-OH, Z-Tyr-OH, and Fmoc-Tyr(tbu)-OH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation